Enhancing physical fitness using recreational soccer and basketball: A parallel-controlled 8-week study involving overweight and obese individuals, with consideration of sex-related interactions - Qi Xu; Rui Miguel Silva; Piotr Zmijewski; Tingyu Li; JianYong Li; LiuXi Yang; Filipe Clemente (Biology of Sport)
The purpose of this study was to examine the effects of 8-week intervention of recreational soccer (SCG) and basketball (BCG) conditioned games, as compared to self-exercise (SECG) and inactive (ICG) control groups, on aerobic capacity, vertical (VJ) and horizontal jump (SLJ) performance, and handgrip maximal strength (HG) in sedentary overweight and obese men and women. Ninety male and female sedentary overweight and obese volunteers (19.8 ± 1.5 years; 27.9 ± 1.8 m/kg 2 ) participated in this experimental parallel controlled design study and were examined on three occasions. Within-group analysis revealed that SCG and BCG significantly ( p < 0.05) improved the performances after 8 weeks in the multistage fitness test (MFT) (23.3 and 19.6%, respectively), HG in right (1.6% and 2.9%) and left hands (1.3 and 1.7%), SLJ (5.8 and 1.4%) and VJT (27.4% and 33.9%). Between-group analysis revealed significantly greater post-intervention improvements in SCG ( p < 0.001) and BCG ( p = 0.043) than ICG in MFT. Improvements in SLJ were greater in SCG ( p < 0.001) and BCG ( p < 0.001) than ICG, being also better in SCG in comparison to SECG ( p = 0.033). VJ performance was significantly better in SCG ( p < 0.001), BCG ( p < 0.001) and SECG ( p = 0.002) than ICG. Only the improvements in HG right ( p = 0.042), and SLJ ( p = 0.016) showed interactions with sex. This study showed that both SCG and BCG are effective interventions for enhancing health related physical fitness, specifically in terms of aerobic capacity and strength. Similar benefits in aerobic capacity could be attained through an 8-week self-regulated activity programme, engaging in activity 3 days per week following a supportive lecture on lifestyle change. Considering sex differences, men demonstrated greater improvements in strength and jumping variables when participating in recreational soccer and basketball. On the other hand, women exhibited more significant enhancements in self-selected activities compared to men, particularly in terms of aerobic capacity.